2015
DOI: 10.1016/j.jcma.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Does radical cystectomy outperform other bladder preservative treatments in elderly patients with advanced bladder cancer?

Abstract: The short- and long-term OS rates of the three modalities were similar in those older than 76 years. Therefore, patients younger than age 76 years are likely to have a better outcome undergoing radical cystectomy for advanced UCB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Laparoscopic and robotic approaches are performed at the selected institutions. Bladder preservative treatment with chemoradiotherapy in patients with advanced bladder cancer is also one of treatment options with the short-and long-term overall survivals similar to that of radical cystectomy in patients older than 76 years (26).…”
Section: Bladder Cancermentioning
confidence: 99%
“…Laparoscopic and robotic approaches are performed at the selected institutions. Bladder preservative treatment with chemoradiotherapy in patients with advanced bladder cancer is also one of treatment options with the short-and long-term overall survivals similar to that of radical cystectomy in patients older than 76 years (26).…”
Section: Bladder Cancermentioning
confidence: 99%
“…Currently, no specific treatment guidelines exist for patients with pancreatic-kidney transplant patients that develop bladder cancer [ 1 , 3 ]. The two most common treatment options for bladder cancer in the general population are RC or bladder TMT [ 10 , 11 ]. For MIBC, the preferred treatment is RC with urinary diversion [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…TMT consists of complete TURBT followed by chemotherapy and radiation [ 4 , 10 ] which evaluated the outcomes and the overall survival rates in 160 patients with bladder cancer treated with either RC, TURBT, TMT, or palliative care with chemotherapy and radiation. The study found no difference in treatment outcomes for advanced UCC with RC and TURBT for patients over 76 years old; however, those under the age of 76 with treated with RC had increased disease-specific survival without recurrence [ 10 ]. Notably, none of these patients had history of SOT which may have altered treatment without chemoradiotherapy restrictions [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the recurrence rate is not low, with an overall 5year survival rate of 15-20% (4,5). Additionally, surgical treatment and chemotherapy are quite limited for advanced bladder cancer (6,7). This high recurrence rate may be partly explained by the poorly understood pathogenesis of BCa (8).…”
Section: Introductionmentioning
confidence: 99%